2014
DOI: 10.20510/ukjpb/2/i6/91171
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro/In Vivo Evaluation and Bioavailability Study of Amitriptyline Hydrochloride from the Optimized Oral Fast Dissolving Films

Abstract: The present investigation was undertaken with the objective of developing fast dissolving film(s) of a tricyclic antidepressant drug amitriptyline hydrochloride in order to improve its bioavailability, optimize its therapeutic action especially when used to treat major depression and to enhance the compliance for the developmentally disable, mentally ill, elderly and pediatric patients. , the study based on cross over design using experimental animals (rabbits). The pharmacokinetic results revealed that the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…While F1 (46.2/43.8 s) and F6 (45.1/43.3 s) showed non-significant diminution (p>0.05) in vitro/in vivo DT this may be due to the fact that the two types of plasticizers enhanced the DT by facilitating the penetration of fluids into the strip, since plasticizer alter the densely packed chains of HPMC texture by forming the polymer structure possessing more pores and less density that breaks at lower force, resulting in faster disintegration of the film [33].…”
Section: Effect Of Different Plasticizer Types On In Vitro/in Vivo Dtmentioning
confidence: 93%
“…While F1 (46.2/43.8 s) and F6 (45.1/43.3 s) showed non-significant diminution (p>0.05) in vitro/in vivo DT this may be due to the fact that the two types of plasticizers enhanced the DT by facilitating the penetration of fluids into the strip, since plasticizer alter the densely packed chains of HPMC texture by forming the polymer structure possessing more pores and less density that breaks at lower force, resulting in faster disintegration of the film [33].…”
Section: Effect Of Different Plasticizer Types On In Vitro/in Vivo Dtmentioning
confidence: 93%
“…The results showed that changing of plasticizer type caused no significant effect (p>0.05) on the in vitro DT of mouth dissolving strips, as show in fig. (7), this may be due to the fact that three types of plasticizer enhanced the disintegration time by facilitating the penetration of fluids into the strip, since plasticizer alter the densely packed chains of HPMC texture by forming a polymer structure possess more pores and less densely that breaks at lower force, resulting in faster disintegration of the film [36].…”
Section: Effect Of Concentrations Of Selected Polymer (Hpmc E5)mentioning
confidence: 99%
“…Accordingly, sublingual medication administration is quicker and more impressible compared to the easily administered oral medication. 23 The thin and extremely permeable membrane of the sublingual mucosa is an appropriate target if a rapid start is favored. Additionally, significant surface area and upper blood flow at this area provide fast availability to the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%